Ramon Lazkano: La ligne de craie - Lazkano, Ramon (Champigny sur Marne l'Ensemble 2e2m, 2011)
How can we get to know the world of a composer today? How can we get to understand what motivates his imagination through the diversity of his works? This eighth book from the collection À la ligne is dedicated to Ramon Lazkano, a Basque composer who was born in 1968.With a very personal voice and the meticulousness of a miniaturist, Lazkano shows a masterful command of textures and temporality as he develops an ethics of a constantly evolving work.
F / E